Hybrids based on borate-functionalized cellulose nanofibers and noble-metal nanoparticles as sustainable catalysts for environmental applications. Issue 21 (26th March 2020) - Esquivel-Peña, Vicente; Guccini, Valentina; Kumar, Sugam; Salazar-Alvarez, German; Rodríguez de San Miguel, Eduardo; de Gyves, Josefina
Abstract : We report the synthesis of supported noble metal nanoparticles on cellulose nanofibers cross-linked with borate as highly efficient sustainable catalysts. Abstract : Polymeric supports from renewable resources such as cellulose nanomaterials are having a direct impact on the development of heterogenous sustainable catalysts. Recently, to increase the potentiality of these materials, research has been oriented towards novel functionalization possibilities. In this study, to increase the stability of cellulose nanofiber films as catalytic supports, by limiting the solubility in water, we report the synthesis of new hybrid catalysts (HC) based on silver, gold, and platinum nanoparticles, and the corresponding bimetallic nanoparticles, supported on cellulose nanofibers (CNFs) cross-linked with borate ions. The catalysts were prepared from metal precursors reduced by the CNFs in an aqueous suspension. Metal nanoparticles supported on CNFs with a spherical shape and a mean size of 9 nm were confirmed by TEM, XRD, and SAXS. Functionalized films of HC-CNFs were obtained by adding a borate solution as a cross-linking agent. Solid-state 11 B NMR of films with different cross-linking degrees evidenced the presence of four different boron species of which the bis-chelate is responsible for the cross-linking of the CNFs. Also, it may be concluded that the bis-chelate and the mono-chelates modify the microstructure of the film increasing the water uptake and enhancing the catalytic activity in the reduction of 4-nitrophenol.